Nutritional status in patients with protein metabolism disorders. Case-control study - Isidro Robredo García; Paula Grattarola; Patricia Correcher Medina; Fátima Abu-Sharif Bohigas; Verónica Vélez García; Isidro Vitoria Miñana; Cecilia Martínez Costa (Anales de Pediatría (English Edition))
Introduction: Patients with protein metabolism disorders (PMDs) require a diet with strict protein control that can affect their growth and development. The aim of the study was to assess nutritional status and growth in patients with PMDs undergoing dietary treatment. Patients and methods: Prospective observational case-control study in 63 patients with PMDs and 63 healthy controls matched for age and sex. We collected data for anthropometric variables (weight, height, BMI, tricipital and subscapular skinfolds, arm and waist circumference) and calculated the corresponding z scores. We also estimated the body fat mass and classified patients into nutritional status categories. Results: The overall analysis found a lower height z score in patients with PMDs and an equal proportion of overweight and obesity with respect to controls (30.2%). When we divided patients with PMDs into 2 groups (phenylketonuria and other aminoacidopathies), we found that patients with phenylketonuria had a height that was similar to the height of controls and significantly higher compared to patients with other aminoacidopathies. When it came to nutritional status, the prevalence of overweight and obesity was greater in the phenylketonuria group (45.5%), while underweight and short stature were more frequent in the group with other aminoacidopathies. Conclusion: Not all patients with PMDs follow the same growth pattern, and their body composition is variable. In our sample, the group of patients with phenylketonuria had an adequate height but also a higher prevalence of overweight and obesity. On the other hand, patients with other aminoacidopathies had a higher prevalence of underweight and lower z scores for height and arm circumference. Resumen: Introducción: Los pacientes con errores innatos del metabolismo de las proteínas (EIMP) requieren una dieta con control proteico estricto que puede condicionar su crecimiento y desarrollo. El objetivo del estudio es valorar el estado nutricional y crecimiento en pacientes con EIMP sometidos a tratamiento dietético. Pacientes y métodos: Estudio observacional prospectivo caso-control en 63 pacientes con EIMP y 63 controles sanos emparejados por edad y sexo. Se obtuvieron datos antropométricos de peso, talla, IMC, pliegues tricipital y subescapular, perímetros del brazo y cintura, y se calcularon sus z-score. Se estimó la grasa corporal y se clasificó el estado nutricional. Resultados: El análisis global mostró un z-score de talla inferior en pacientes con EIMP, e igual proporción de sobrepeso y obesidad respecto a controles (30,2%). Al dividir los pacientes con EIMP en dos grupos (fenilcetonuria y otras aminoacidopatías) se observó que los pacientes con fenilcetonuria tuvieron una talla similar a los controles y significativamente superior a los pacientes con otras aminoacidopatías. Al clasificar el estado de nutrición, la prevalencia de sobrepeso y obesidad fue superior en el grupo de fenilcetonuria (45,5%), mientras que los pacientes más desnutridos y con talla baja se encontraron en el grupo de otras aminoacidopatías. Conclusión: No todos los pacientes con EIMP siguen un mismo patrón de crecimiento y su composición corporal es variable. En esta muestra, los pacientes con fenilcetonuria tienen una talla adecuada y mayor incidencia de sobrepeso y obesidad. Sin embargo, otras aminoacidopatías presentan mayores tasas de desnutrición y menor z-score de talla y perímetro del brazo.